2016
DOI: 10.1186/s12903-016-0311-z
|View full text |Cite
|
Sign up to set email alerts
|

The differences in healthcare utilization for dental caries based on the implementation of water fluoridation in South Korea

Abstract: BackgroundThere were some debates about the water fluoridation program in South Korea, even if the program had generally substantial effectiveness. Because the out-of-pocket expenditures for dental care were higher in South Korea than in other countries, an efficient solution was needed. Therefore, we examined the relationship between the implementation of water fluoridation and the utilization of dental care.MethodsWe used the National Health Insurance Service National Sample Cohort. In this study, data final… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 27 publications
(29 reference statements)
0
8
0
Order By: Relevance
“…[59][60][61][62] Additional adult studies included in the Canadian review assessed caries severity (DMFT/S), [63][64][65][66] caries prevalence, 67 tooth loss 68,69 and dental service use. 70,71 Of these 15 primary studies, 9 were assessed as being of 'acceptable' quality by the review authors and 7 as 'low' quality. 49,51 The studies were ecological [57][58][59][60][61][62]65,67,70,71 and cross-sectional.…”
Section: Systematic Reviewsmentioning
confidence: 99%
See 4 more Smart Citations
“…[59][60][61][62] Additional adult studies included in the Canadian review assessed caries severity (DMFT/S), [63][64][65][66] caries prevalence, 67 tooth loss 68,69 and dental service use. 70,71 Of these 15 primary studies, 9 were assessed as being of 'acceptable' quality by the review authors and 7 as 'low' quality. 49,51 The studies were ecological [57][58][59][60][61][62]65,67,70,71 and cross-sectional.…”
Section: Systematic Reviewsmentioning
confidence: 99%
“…70,71 Of these 15 primary studies, 9 were assessed as being of 'acceptable' quality by the review authors and 7 as 'low' quality. 49,51 The studies were ecological [57][58][59][60][61][62]65,67,70,71 and cross-sectional. [64][65][66]68 The authors of the Australian review concluded that the quality of the evidence was 'low or very low', but it was consistent and 'indicates that water fluoridation improves the dental health of children and adults'.…”
Section: Systematic Reviewsmentioning
confidence: 99%
See 3 more Smart Citations